PARTISIPASI MASYARAKAT DALAM PROGRAM POKOK PEMBERDAYAAN KESEJAHTERAAN KELUARGA DI NAGARI SUNGAI DAREH KECAMATAN PULAU PUNJUNG - Eka Puspita; Rini Parmila Yanti; Handika Aditama (Jurnal Public Administration, Business and Rural Develoment Planning, 2022)
Based on the descriptions in the previous chapters, the authors draw the following conclusions: 1) Community Participation in the Main Program of Family Welfare Development in Nagari Sungai Dareh, Pulau Punjung District, namely a) Participation of thoughts, namely the proposal to make a toga planted with red ginger for a competition to make red ginger candy and work together in case of disaster. b) Participation of personnel, namely participating in mutual cooperation in cleaning the environment and participating in helping communities affected by floods, c) Participating in property, namely by giving the community a table for posyandu activities in Jorong Koto Tangah, donating a plot of land for Poskesri development, donate kitchen utensils that are used as PKK assets, namely glasses, plates and cauldrons and donate assets in the form of money and also become monthly donors, d) Skill participation, namely skills in making bags, purses, baskets and tablecloths, cooking skills and making cakes so that the community can help the household economy. 2) Factors Affecting Community Participation in the Main Program for Family Welfare Empowerment in Nagari Sungai Dareh, Pulau Punjung District, namely a) Communication that fosters effective or successful understanding. b) Changes in attitudes, opinions and behavior caused by understanding that raises awareness. c) Awareness based on calculations and considerations. d) Willingness to do something that grows from the bottom of one's heart without being forced by others. e) There is a sense of responsibility towards the common interest. Based on the conclusions above, the authors provide the following suggestions: 1) It is hoped that the PKK will involve all elements of society in every program implemented. 2) To be more creative in utilizing all available resources in the surrounding environment, so that all program activities in various fields driven by the PKK driving team can run well